SUPERMARKET THEATRES, OVERSUPPLY OF LABOUR AND NEW HOLDERS OF CAPITAL IN GREEK THEATRE DURING THE DEBT CRISIS (2010-2019) - Angelopoulos, Tasos (Politeia, 2023)
Using Pierre Bourdieu’s field methodology, the article tries to chart the rearrangements within the theatrical field in Greece during the decade of the economic crisis (2010-2019). The article identifies the distortions of the Greek theatrical market, such as the oversupply of labour and the replacement of theatres with an artistic imprint by the here called “supermarket” theatres. In addition, we follow the attempt of the “Stegi” by the Onassis Foundation to emerge as the central holder of the (symbolic) capital within this theatrical field, occupying the place Amore Theater used to have. Finally, it is concluded that the theatrical field - and because of the pandemic that followed the economic crisis – resists against fully mapping, as new initiatives and groupings are still taking place within it.